2022
DOI: 10.3390/jcm11040968
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease and Risk of Macro- and Microvascular Complications in Patients with Type 2 Diabetes

Abstract: Non-alcoholic fatty liver disease (NAFLD) is considered the hepatic manifestation of metabolic syndrome. To date, NAFLD is the most frequent chronic liver disease seen day by day in clinical practice across most high-income countries, affecting nearly 25–30% of adults in the general population and up to 70% of patients with T2DM. Over the last few decades, it clearly emerged that NAFLD is a “multisystemic disease” and that the leading cause of death among patients with NAFLD is cardiovascular disease (CVD). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 89 publications
(177 reference statements)
0
32
0
1
Order By: Relevance
“…The relationship between retinopathy and MAFLD, however, remains conflicting with limited available studies [ 24 ]. Regarding macrovascular complications, cardiovascular disease remains the most common cause of death among patients with MAFLD, and previous studies have demonstrated that patients with MAFLD are at a higher risk for CVD events, despite adjusting for relating confounders [ 24 ]. On the other hand, in patients with T2D, MAFLD progresses to cirrhosis at a much faster pace [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between retinopathy and MAFLD, however, remains conflicting with limited available studies [ 24 ]. Regarding macrovascular complications, cardiovascular disease remains the most common cause of death among patients with MAFLD, and previous studies have demonstrated that patients with MAFLD are at a higher risk for CVD events, despite adjusting for relating confounders [ 24 ]. On the other hand, in patients with T2D, MAFLD progresses to cirrhosis at a much faster pace [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has illustrated a negative correlation between anti-lipid therapy and AIP level [ 24 ]. Therefore, compared to the aforementioned studies [ 10 , 11 , 13 ], we went one step further and included anti-lipid therapy as a confounding factor in our analysis and still managed to demonstrate a high odds ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the direct proarrhythmic effects of adipose secretome, chronic obesity confers arrhythmic risks via systemic metabolic complications, such as non-alcoholic fatty liver disease (NAFLD) ( 21 , 22 ). NAFLD has been linked to higher rates of adverse cardiovascular outcomes ( 23 ) that include greater risks of atrial fibrillation ( 24 26 ), QTc prolongation ( 27 , 28 ), and VA ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD has been linked to higher rates of adverse cardiovascular outcomes ( 23 ) that include greater risks of atrial fibrillation ( 24 26 ), QTc prolongation ( 27 , 28 ), and VA ( 29 , 30 ). Insulin resistance and dysregulated lipid metabolism resulting in release of pro-inflammatory, -fibrotic and -oxidising hepatic mediators may underpin these observations ( 22 , 31 , 32 ). Furthermore, NAFLD favours epicardial fat accumulation resulting in cardiac lipotoxicity, fatty infiltration, fibrosis, and yet more secretion of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%